Proceso atención de enfermería en adulto mayor con insuficiencia cardiaca más Sars-Covid19. - Mero Tumbaco, Priscila Monserrate (2021)
Heart failure is a disease that affects a considerable amount of the population and that becomes a public health problem both because of the high prevalence rates and even because of the cost of the treatments that ends up making it difficult to cover all of them. the patients. Its clinical picture develops from the irregular functioning of the heart where there is not an adequate pumping of the blood and after this, symptoms and signs such as dyspnea or fatigue may appear. COVID19 disease determined as a pandemic, also results as a public health problem, with high rates of infections and in addition to deaths, studies are still being developed to find a definitive cure, however, there are already vaccines that are being administered to the Its main clinical picture is respiratory, however, depending on the adjacent clinical diseases, the patient's symptoms may vary. These two diseases are related to each other and to what is happening today, it is of utmost importance to pay attention to the symptoms in such a way that it can be deduced if the patient may be presenting a picture of evolution of COVID19, a point from which it can be The starting point is that the patient with heart failure usually has dyspnea but if this is accompanied by a cough or fever plus a possible contact with a positive COVID patient, it would give an indication that the patient is a suspected case, for which we proceed to act immediately in order to prevent your condition from worsening.